Temporal Changes in Invasive Group B Streptococcus Serotypes: Implications for Vaccine Development - Dangor, Ziyaad; Cutland, Clare L.; Izu, Alane; Kwatra, Gaurav; Trenor, Siobhan; Lala, Sanjay G.; Madhi, Shabir A. (PLOS ONE, 2016)
Introduction There is a paucity of longitudinal data on the serotype-specific burden of invasive group B Streptococcus (GBS) disease from low-middle income countries, which could inform selection of vaccine epitopes. Methods From 2005 to 2014, infants less than 90 days of age with invasive GBS disease were identified through sentinel laboratory and hospital admission surveillance at Chris Hani Baragwanath Academic Hospital in Soweto, South Africa. Results We identified 820 cases of invasive GBS disease, including 55% among newborns <7 days age (i.e. early-onset disease; EOD). The overall incidence (per 1,000 live births) of invasive GBS disease was 2.59 (95% CI: 2.42–2.77), including 1.41 (95% CI: 1.28–1.55) for EOD and 1.18 (95% CI: 1.06–1.30) in infants 7–89 days age (late-onset disease). Year-on-year, from 2005 to 2014, we observed a 9.4% increase in incidence of serotype Ia invasive disease (RR: 1.09; 95% CI: 1.04–1.15; p<0.001), and a 7.4% decline in serotype III invasive disease (RR: 0.93; 95% CI: 0.90–0.96; p<0.001). Overall, serotypes Ia (28.2%), III (55.4%) and V (7.9%) were the commonest disease causing serotypes. Conclusions The incidence of invasive GBS disease has remained persistently high in our setting, with some changes in serotype distribution, albeit mainly involving the same group of dominant serotypes.